Bottom‐Reached Near‐Inertial Waves Induced by the Tropical Cyclones, Conson and Mindulle, in the South China Sea. Issue 6 (2nd June 2022) - Ma, Yonggui; Wang, Dongxiao; Shu, Yeqiang; Chen, Ju; He, Yunkai; Xie, Qiang
Abstract: Moored current observations in the northwestern South China Sea (SCS) captured two events of near‐inertial waves (NIWs) induced by the tropical cyclones Conson and Mindulle, which propagated to the seafloor from the base of the mixed layer. The time taken by the Conson‐induced near‐inertial kinetic energy (NIKE) to reach the bottom of the ocean was approximately 12 days. This NIKE was twice as fast as the Mindulle‐induced NIKE to reach the bottom of the ocean, which was mainly dependent on the properties of the NIWs deeply affected by the background vorticity. The NIWs in the upper layer induced by Conson/Mindulle showed a significant blue/red shift (1.07/0.85 f f ) as the observation site was located outside/within an exceptional anticyclonic eddy. The bottom NIWs showed an obvious blue shift, aligning with the result of ray tracing, which revealed that the bottom wave packets originated from higher latitudes. We estimated an NIW vertical energy flux of up to 0.22 m W m −2 in the abyssal ocean, which represents about 29% of the upper layer NIKE. The reached seabed NIWs had high vertical shear and might dissipate locally and play an important role in the maintenance of deep mixing of the SCS. Plain Language Summary: Near‐inertial waves (NIWs) are low‐frequency internal waves in the ocean. Based on moored instruments, we observed strong NIW signals in the deep layer of the South China Sea after tropical cyclones Conson and Mindulle. It was estimated that up to 22%–29% of the NIW kinetic energy in the upper ocean penetrated near the bottom boundary. The strong vertical velocity shear induced by the NIWs near the bottom indicated that NIW kinetic energy might be dissipated near the bottom boundary layer, which would contribute to sustaining the strong mixing as well as deep circulation. This study gives observed evidence that the extreme atmospheric forcing influences the deep ocean. Key Points: Penetrating abyssal near‐inertial kinetic energy (NIKE) was observed in the northwestern South China Sea (SCS) Approximately 22%–29% of NIKE induced by tropical cyclones propagated to the seabed with a water depth of 1, 400 m in the northwestern SCS Most of the deep NIKE was found to dissipate into turbulence near the seabed